Free sugar intake is associated with reduced proportion of circulating invariant natural killer T cells among women experiencing overweight and obesity - Alhamawi, Renad M.; Almutawif, Yahya A.; Aloufi, Bushra H.; Alotaibi, Jory F.; Alharbi, Manar F.; Alsrani, Nura M.; Alinizy, Razan M.; Almutairi, Waad S.; Alaswad, Wed A.; Eid, Hamza M. A.; Mumena, Walaa A. (Frontiers in Immunology, 2024)
Background: Higher prevalence of obesity has been observed among women compared to men, which can be explained partly by the higher consumption of sweets and physical inactivity. Obesity can alter immune cell infiltration, and therefore increase the susceptibility to develop chronic inflammation and metabolic disorders. In this study, we aimed to explore the association between free sugar intake and other unhealthy lifestyle habits in relation to the proportion of circulating iNKT cells among women with healthy weight and women experiencing overweight and obesity. Methods: A cross-sectional study was conducted on 51 Saudi women > 18 years, wherein their daily free sugar intake was assessed using the validated Food Frequency Questionnaire. Data on smoking status, physical activity, and supplement use were also collected. Anthropometric data including height, weight, waist circumference were objectively measured from each participants. The proportion of circulating iNKT cells was determined using flow cytometry. Results: Smoking, physical activity, supplement use, and weight status were not associated with proportion of circulating iNKT cells. Significant association was found between proportion of circulating iNKT cells and total free sugar intake and free sugar intake coming from solid food sources only among women experiencing over weight and obesity (Beta: -0.10: Standard Error: 0.04 [95% Confidence Interval: -0.18 to -0.01], p= 0.034) and (Beta: -0.15: Standard Error: 0.05 [95% Confidence Interval: -0.25 to -0.05], p= 0.005), respectively. Conclusion: Excessive free sugar consumption may alter iNKT cells and consequently increase the risk for chronic inflammation and metabolic disorders. Deleted: (Ref).